Beyond Betrayal: Unveiling the Survivor’s Guilt and Trauma in K.R. Meera’s The Gospel of Judas - Srujini Battu (ILN Journal: Indian Literary Narratives, 2024)
Trauma is commonly associated with the experiences of loss. In the face of loss, individuals come face-to-face with the absence of a cherished entity. As a result, they often develop a deep sense of detachment and longing for the lost object. Over time, victims seek alternative means to fill the void left by the lost object, as they are unable to find comparable gratification elsewhere. However, this quest for satisfaction ultimately proves futile, resulting in an ongoing cycle of disappointment for the victim. Various modes of representation are utilized to delve into the intricate relationship between the enactment of trauma and its subsequent resolution, especially literature. This article uses a psychoanalytic approach to analyze survivor’s guilt and its trauma in The Gospel of Yudas. In the novel, the characters Das and Prema endure profoundly distressing experiences. Das’ post-traumatic stress disorder (PTSD) is palpable through his actions, persistently recovering bodies from lakes and rivers. He is tormented by the agonizing recollection of his beloved's demise, ensnared in his own past. Prema, displaying profound empathy for Das, also suffers from trauma. She exhibits symptoms of secondary trauma, afflicted not only by her unreciprocated love for Das but also by her profound empathetic bond with him. Survivor guilt is a significant element in PTSD. The survivor guilt may contribute to a complex grief reaction.